Review of the genus Epicrocis Zeller, 1848 in China (Lepidoptera, Pyralidae), with descriptions of three new species - Liu, Hongxia; Li, Houhun (Zootaxa, 2020)
The genus Epicrocis Zeller, 1848 is reviewed in China. Three species are described as new: Epicrocis datianensis sp. nov., E. maculata sp. nov. and E. flabelloformis sp. nov. Epicrocis pramaoyensis Bae & Qi, 2015 and E. metallopa (Lower, 1898) are newly recorded in China. Images of adults and genitalia are provided, along with a key and a distribution map to all the known Chinese species.